Educação musical, criatividade e autonomia do sujeito: um estudo de caso - Andrade, Leandro de Abreu (2021)
As art is a form of expression and a social construction of aesthetic and cultural value inherent to the human being and responsible for the construction of the being's identity, some questions arose. How can learning music help to build an individual's identity? How can this individual recognize and recognize the other through musical-educational experiences? How can music education contribute to the human formation of the individual, in order to encourage him to have an autonomous posture and a free and creative thought? Based on these questions, a survey was carried out with the general objective of studying the educational processes at the School of Music Chiquita Braga and sought to verify the contribution of such processes to the development of autonomy and creativity of its students. The specific objectives of this study were: to outline the socio-educational profile of music students at the Chiquita Braga Music School; to analyze the perception of the various researched subjects about the teaching and learning process that took place within the Chiquita Braga School of Music; understand the correlation of pedagogical practices in the context of the educational process with the conceptual categories autonomy and creativity within the Chiquita Braga School of Music. For this work, the thoughts and concepts related to the human formation of the individual proposed by Freire (1987), who brought us the conceptual category of autonomy, and by the music educator Hans-Joachim Koellreutter (2018a, 2018b, 2018c, 2018d, 2018e, 2018f) were used as a theoretical framework, which provided us with the conceptual category of creativity. These authors idealized a pedagogy of a libertarian character that promotes the inquisitive, reflective, autonomous and creative spirit of the human being, through education. The methodological procedures used were of a qualitative nature, using the case study method. As data collection instruments, questionnaires were applied and interviews were carried out. Data treatment used the content analysis techniques proposed by Bardin (1979).